Three-month risk-benefit profile of anticoagulation after stroke with atrial fibrillation: The SAMURAI-Nonvalvular Atrial Fibrillation (NVAF) study. Issue 5 (July 2016) - Arihiro, Shoji; Todo, Kenichi; Koga, Masatoshi; Furui, Eisuke; Kinoshita, Naoto; Kimura, Kazumi; Yamagami, Hiroshi; Terasaki, Tadashi; Yoshimura, Sohei; Shiokawa, Yoshiaki; Kamiyama, Kenji; Takizawa, Shunya; et al.
Aims: This study was performed to determine the short-term risk-benefit profiles of patients treated with oral anticoagulation for acute ischemic stroke or transient ischemic attack using a multicenter, prospective registry. Methods: A total of 1137 patients (645 men, 77 ± 10 years old) with acute ischemic stroke/transient ischemic attack taking warfarin (662 patients) or non-vitamin K antagonist oral anticoagulants (dabigatran in 205, rivaroxaban in 245, apixaban in 25 patients) for nonvalvular atrial fibrillation who completed a three-month follow-up survey were studied. Choice of anticoagulants was not randomized. Primary outcome measures were stroke/systemic embolism and major bleeding. Results: Both warfarin and non-vitamin K antagonist oral anticoagulants were initiated within four days after stroke/transient ischemic attack onset in the majority of cases. Non-vitamin K antagonist oral anticoagulant users had lower ischemia- and bleeding-risk indices (CHADS2, CHA2 DS2 -VASc, HAS-BLED) and milder strokes than warfarin users. The three-month cumulative rate of stroke/systemic embolism was 3.06% (95% CI 1.96%–4.74%) in warfarin users and 2.84% (1.65%–4.83%) in non-vitamin K antagonist oral anticoagulant users (adjusted HR 0.96, 95% CI 0.44–2.04). The rate of major bleeding was 2.61% (1.60%–4.22%) and 1.11% (0.14%–1.08%), respectively (HR 0.63, 0.19–1.78); that for intracranial hemorrhage was marginally significantly lower in non-vitamin K antagonist oral anticoagulant users (HR 0.17, 0.01–1.15). Major bleeding did not occur in non-vitamin K antagonist oral anticoagulant users with a CHADS2 score <4 or those with a discharge modified Rankin Scale score ≤2. Conclusions: Stroke or systemic embolism during the initial three-month anticoagulation period after stroke/transient ischemic attack was not frequent as compared to previous findings regardless of warfarin or non-vitamin K antagonist oral anticoagulants were used. Intracranial hemorrhage was relatively uncommon in non-vitamin K antagonist oral anticoagulant users, although treatment assignment was not randomized. Early initiation of non-vitamin K antagonist oral anticoagulants during the acute stage of stroke/transient ischemic attack in real-world clinical settings seems safe in bleeding-susceptible Japanese population.